ADVANTAGES FOR THE IMPLEMENTATION OF ERP BASED INFORMATION SYSTEMS IN SERVICE COMPANIES - Widiastuti, Maria (Jurnal Ilmu Manajemen Terapan, 2020)
This article is made is to explain that in general service companies operationally have a simpler business process, compared to trading or manufacturing companies, still need an integrated information system. And the importance of Information Systems for the running of the company, so that it can facilitate the management in making decisions related to the performance of all departments or sections in the company. Integrated information systems can help the management in making company operational reporting, internal control processes over the running of the company's operations, and can provide information needed by management in formulating the company's business development strategy. Companies in developing information systems that can achieve these objectives can use an ERP-based information system (Enterpise Resousch Planning).